2021
DOI: 10.3390/healthcare9060625
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Testing and Contact-Tracing to Counter COVID-19 Pandemic: Designed Experiments of Agent-Based Simulation

Abstract: The widespread outbreak of the novel coronavirus disease COVID-19 has posed an enormous threat to global public health. A different set of policy interventions has been implemented to mitigate the spread in most countries. While the use of personal protective equipment and social distancing has been specifically emphasized, South Korea has deployed massive testing and contact-tracing program from the early stage of the outbreak. This study aims at investigating the effectiveness of testing and contact-tracing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It is worth noting that the virus spread reduction due to contact tracing in the present small-world network model is much more significant than that in the continuous deterministic models. For example, results 25 , 26 from continuous deterministic models with comparable input parameters show a much less profound reduction of infection cases. A specific example 26 is with a 40% testing coverage, 1 day turnaround time of test results, and 60% contact tracing ratio, the peak infection number is reduced by only 50%, a level much lower than Figs 2 and 4 imply.…”
Section: Modeling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the virus spread reduction due to contact tracing in the present small-world network model is much more significant than that in the continuous deterministic models. For example, results 25 , 26 from continuous deterministic models with comparable input parameters show a much less profound reduction of infection cases. A specific example 26 is with a 40% testing coverage, 1 day turnaround time of test results, and 60% contact tracing ratio, the peak infection number is reduced by only 50%, a level much lower than Figs 2 and 4 imply.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…For example, results 25 , 26 from continuous deterministic models with comparable input parameters show a much less profound reduction of infection cases. A specific example 26 is with a 40% testing coverage, 1 day turnaround time of test results, and 60% contact tracing ratio, the peak infection number is reduced by only 50%, a level much lower than Figs 2 and 4 imply.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…However, such a model only considers a few parameters in addition to the SEIR model, such as the CT rate, success rate of CT, and average daily contacts. The susceptible-exposed-infectious-confirmed-recovered (SEICR) model is adopted in [14] to the agent-based modeling (ABM) as an alternative to the theoretical modeling to deal with the complexity of the related factors. However, the agent-based modeling or simulation for applicable sensing mechanisms arising from COVID-19 with an IoT architecture has not been studied in the literature.…”
Section: Interacting Network and Ct Modelingmentioning
confidence: 99%
“…Additionally, a review of the types and usefulness of various compartmental models in predicting COVID-19 spread was conducted by Padmanabhan et al ( Padmanabhan et al, 2021 ). The effects of testing, isolation, and compliance have also been examined in the context of ABMs, as in ( Almagor & Picascia, 2020 ; Kim & Koo, 2021 ; Moghadas et al, 2020 ; Álvarez & Rojas-Galeano, 2020 ). In particular, Moghadas et al ( Moghadas et al, 2020 ) suggested that mass testing of the asymptomatic individuals is necessary to mitigate the spread of COVID-19; this helps slow the disease spread and thus bring the pandemic under control.…”
Section: Introductionmentioning
confidence: 99%